The Effect of a New Therapy for Children with Tics Targeting Underlying Cognitive, Behavioral, and Physiological Processes - Leclerc, Julie B.; O’Connor, Kieron P.; J.-Nolin, Gabrielle; Valois, Philippe; Lavoie, Marc E. (Frontiers in Psychiatry, 2016)
Tourette disorder (TD) is characterized by motor and vocal tics and children with TD tend to present a lower quality of life than neurotypical children. This study applied a manualized treatment for childhood tics disorder Facotik to a consecutive case series of children aged 8-12 years. The Facotik therapy was adapted from the adult Cognitive and Psychophysiological program validated on a range of subtypes of tics. This approach aims to modify the cognitive-behavioral and physiological processes against which the tic occurs rather than only addressing the tic behavior. The Facotik therapy lasted 12-14 weeks. Each week 90-minute session contained 20 minutes of parental training. The therapy for children followed 10 stages including: awareness training; improving motor control; modifying style of planning; cognitive and behavioral restructuring; and relapse prevention. Thirteen children were recruited as consecutive referrals from the general population and seven cases completed therapy and post-treatment measures. Overall results showed a significant decrease in symptom severity as measured by the YGTSS and the TSGS. However, there was a discrepancy between parent and child rating, with some children perceiving an increase in tics, possibly due to improvement of awareness along therapy. They were also individual changes on adaptive aspects of behavior as measured with the BASC-2, and there was variability among children. All children maintained or improved self-esteem post treatment. The results confirm the conclusion of a previous pilot study which contributed to the adaptation of the adult therapy. In summary, the Facotik therapy reduced tics in children. These results underline that addressing processes underlying tics may complement approaches which target tics specifically.